2018
DOI: 10.1002/asi.24019
|View full text |Cite
|
Sign up to set email alerts
|

Researchers' uses of and disincentives for sharing their research identity information in research information management systems

Abstract: This study examined how researchers used research information systems (RIMSs) and the relationships among researchers' seniority, discipline, and types and extent of RIMS use. Most researchers used RIMSs to discover research content. Fewer used RIMSs for sharing and promoting their research. Early career researchers were more frequent users of RIMSs than were associate and full professors. Likewise, assistant professors and postdocs exhibited a higher probability of using RIMSs to promote their research than d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Haustein and Larivière (2014) found that the majority of Mendeley users in four disciplines (i.e., biomedical research, clinical medicine, health, and psychology) were junior scholars (i.e., doctoral students, postgraduate students, and postdocs). Stvilia and his collaborators (Stvilia et al, 2018a) also found that assistant professors and postdocs had higher usage in RIMS than full professors. However, this study considered only three seniority levels (i.e., assistant, associate, and full professors) that do not fully capture researchers' seniority range in academia.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Haustein and Larivière (2014) found that the majority of Mendeley users in four disciplines (i.e., biomedical research, clinical medicine, health, and psychology) were junior scholars (i.e., doctoral students, postgraduate students, and postdocs). Stvilia and his collaborators (Stvilia et al, 2018a) also found that assistant professors and postdocs had higher usage in RIMS than full professors. However, this study considered only three seniority levels (i.e., assistant, associate, and full professors) that do not fully capture researchers' seniority range in academia.…”
Section: Discussionmentioning
confidence: 95%
“…Engaging researchers in the management of their RIMS profiles can bring the necessary knowledge of disciplinary context to the curation of their research information. To achieve that goal, however, a non-mandatory RIMS needs to make researchers' engagement with the RIMS low cost (Stvilia et al, 2018a). Hence, TAMU Libraries' Scholars project team slowly increased the number of curated faculty profiles in Scholars by going department by department and college by college and being guided by their feedback, needs, and comments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The identified information-quality problems included five types of problems (inaccuracy, irrelevance, outdatedness, incompleteness and spuriousness) and twelve quality criteria that the researchers perceived to be important. In a later study, Stvilia et al (2018) refined the interview questions and developed a questionnaire survey. The questionnaire was completed by 412 participants with a response rate of 25%.…”
Section: Related Researchmentioning
confidence: 99%
“…Concerns over privacy, in other words, were not identified as a significant issue. 18 Several existing case studies on RIM Systems focus on aspects other than privacy, such as integration with institutional repositories, 19 implementation to fulfill publications reporting needs, 20 motivations for engaging with RIM Systems, 21 and library roles. 22…”
Section: Literaturementioning
confidence: 99%